PERSEPSI GURU TENTANG MANAJEMEN PESERTA DIDIK SEKOLAH DASAR NEGERI GUGUS II KECAMATAN LUBUK SIKARAH KOTA SOLOK - Nurul Rahmi (Universitas Negeri Padang, 2014)
This study aimed to describe the teacher's perception of student management Cluster II Elementary School District of Solok Sikarah Lubuk in terms of acceptance of new learners, learner data recording, grouping students and coaching learners. The population is 138 teacher and 35 samples were taken from 25% of the population. The research instrument was a questionnaire in the form of a Likert scale validity has been tested and reliable. Data were analyzed using the mean score (mean). The results of this study are teachers' perceptions about the management of public elementary school students Force II Solok District of Lubuk Sikarah been good. Key word : student management